Pre-cooling of boar semen before transport in a hot environment enhances biosafety - Reckinger, Florian; Luther, Anne-Marie; Verspohl, Jutta; Artavia, Johann Lotz; Waberski, Dagmar (Frontiers in Microbiology, 2025)
In a changing climate, the increase in temperature of boar semen doses during shipping to sow farms is a concern. Temperatures above the recommended storage range of 16–18°C for boar semen may compromise sperm quality due to bacterial growth and heat stress. The aim was to investigate whether cooling semen doses to 5°C prior to simulated transport at an environmental temperature of 30°C could inhibit bacterial growth and maintain sperm quality. Extended semen was treated in three variants: with and without pre-cooling to 5°C before simulated transport the next day at 30°C, and a control held stationary at 17°C. Transport vibration was simulated by shaking the semen doses for 6 h on an orbital shaker. Thereafter, all samples were stored at 17°C for 144 h. Pre-cooling efficiently delayed exponential microbial growth in samples spiked with resistant bacterial species. Although sperm motility was reduced by ~13 % in the pre-cooled samples, minimum quality requirements were fulfilled. Sperm membrane and mitochondrial membrane potential were not affected by the treatment. In conclusion, pre-cooling of semen before transport in a hot environment enhances biosafety of semen doses, while maintaining quality standards for use in artificial insemination.